'Repeat after me!': child's play, immaturity and resistance. Issue 2 (4th May 2022) - Baspehlivan, Uygar
Abstract: "Children are our future". This is the dominant understanding of childhood we have today. The child, is an investment in the future. The investment that will yield the nation, the economy and the world with the continuity that it wants and requires. The future is secured by the child. This investment, however, is never secure. In fact, the investment in the child is often also a cause of debilitating insecurity. The child is feared, worried about and paranoically obsessed about. Is this all there is to the child? Whatever happens to "play" – the quintessential activity of the modern child- in this in/secure investment? In this intervention, I critique these investments by gesturing towards a disentanglement of the child away from such spectacles of crisis towards novel associations with the child as a site of political possibility. Children's play not only comprise the pre-mature through which a future may or may not be actualised, I argue, but also offer a revelatory political possibility through its negation of the mature; in enacting the "im-mature". The way the child resists maturity, the modes through which they resist, question, play with and negate the law and the discourse of the mature and consequently the law of the nation gestures towards alternative political becomings. Becomings through which we may find, imagine and exercise practices subversive of authoritative structures which we are all continually governed and disciplined by.